Phase I or II Study of Ribociclib in Combination With Topotecan-Temozolomide or Everolimus in Children With Advanced Malignancies: Arms A and B of the AcSé-ESMART Trial. Issue 32 (10th November 2021) - Bautista, Francisco; Paoletti, Xavier; Rubino, Jonathan; Brard, Caroline; Rezai, Keyvan; Nebchi, Souad; Andre, Nicolas; Aerts, Isabelle; De Carli, Emilie; van Eijkelenburg, Natasha; Thebaud, Estelle; Corradini, Nadege; et al.
Abstract : PURPOSE: AcSé-ESMART is a proof-of-concept, phase I or II, platform trial, designed to explore targeted agents in a molecularly enriched cancer population. Arms A and B aimed to define the recommended phase II dose and activity of the CDK4/6 inhibitor ribociclib with topotecan and temozolomide (TOTEM) or everolimus, respectively, in children with recurrent or refractory malignancies. PATIENTS AND METHODS: Ribociclib was administered orally once daily for 16 days after TOTEM for 5 days (arm A) or for 21 days with everolimus orally once daily continuously in a 28-day cycle (arm B). Dose escalation followed the continuous reassessment method, and activity assessment the Ensign design. Arms were enriched on the basis of molecular alterations in the cell cycle or PI3K/AKT/mTOR pathways. RESULTS: Thirty-two patients were included, 14 in arm A and 18 in arm B, and 31 were treated. Fourteen patients had sarcomas (43.8%), and 13 brain tumors (40.6%). Main toxicities were leukopenia, neutropenia, and lymphopenia. The recommended phase II dose was ribociclib 260 mg/m 2 once a day, temozolomide 100 mg/m 2 once a day, and topotecan 0.5 mg/m 2 once a day (arm A) and ribociclib 175 mg/m 2 once a day and everolimus 2.5 mg/m 2 once a day (arm B). Pharmacokinetic analyses confirmed the drug-drug interaction of ribociclib on everolimus exposure. Two patients (14.3%) had stable disease as best response in arm A, and seven (41.2%) in arm B, including one patient with T-acute lymphoblastic leukemia with significant blast count reduction. Alterations considered for enrichment were present in 25 patients (81%) and in eight of nine patients with stable disease; the leukemia exhibited CDKN2A/B and PTEN deficiency. CONCLUSION: Ribociclib in combination with TOTEM or everolimus was well-tolerated. The observed activity signals initiated a follow-up study of the ribociclib-everolimus combination in a population enriched with molecular alterations within both pathways.